2021
DOI: 10.1177/20427530211027722
|View full text |Cite
|
Sign up to set email alerts
|

Perception on research methods course’s online environment and self-regulated learning during the COVID-19 pandemic

Abstract: The COVID-19 pandemic brought an education crisis that forced schools to abruptly shift to online distance learning. Regardless of the challenges in this migration, the teaching–learning process should continue. Self-regulated learning skills are essential in learning in an online environment; hence, the study aims to explore learners’ perception in an online learning environment, self-regulated learning skills, and academic achievement during a research methods course. Perception on the online learning enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…At the time of data collection, students in our study had just transitioned back to in-person instruction after a semester-long online learning due to the pandemic, and they may have used different SRL strategies in response to the specific classroom context. Although MSLQ-CAL-LS is found to adequately measure SRL, we call for a systematic statistical approach (e.g., measurement invariance) to refine MSLQ-CAL-LS that can be applicable in both online and in-person learning because when the context changes, so does instruction [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…At the time of data collection, students in our study had just transitioned back to in-person instruction after a semester-long online learning due to the pandemic, and they may have used different SRL strategies in response to the specific classroom context. Although MSLQ-CAL-LS is found to adequately measure SRL, we call for a systematic statistical approach (e.g., measurement invariance) to refine MSLQ-CAL-LS that can be applicable in both online and in-person learning because when the context changes, so does instruction [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…However, academic achievement dropped when lessons began to become more complex; this was attributed to the stagnant self-regulation of students throughout the online course. The study recommended that online courses promote self-regulation to maintain the academic achievement of learners (Calamlam et al, 2022). Despite the promises of online learning as a possible alternative to more traditional approaches, studies before and during the COVID-19 pandemic typically reported limitations.…”
Section: Online Distance Learningmentioning
confidence: 99%
“…Interventions to promote SRL are necessary for an online learning environment; failure to provide one is believed to have detrimental effects on academic achievement (Calamlam et al, 2022). Providing learners with adequate resources and opportunities to promote SRL strategies may contribute to the learner's online learning readiness and acceptance (Yeh et al, 2019).…”
Section: Online Distance Learningmentioning
confidence: 99%
See 2 more Smart Citations